Water and radiation use efficiencies in maize: breeding effects on single-cross Argentine hybrids released between 1980 and 2012 - Curin, Facundo; Severini, Alan David; Gonzalez, Fernanda Gabriela; Otegui, María Elena (Elsevier, 2019)
Water deficit has been signaled as an important determinant of grain yield (GY) gaps between potential and actual GYs. Breeding for improved water as well as solar radiation productivities is a sustainable means to reduce this gap. The aim of this study was to evaluate breeding effects on GY and its physiological determinants, including water (WUE) and radiation (RUE) use efficiencies, of temperate maize hybrids grown under a wide range of environmental conditions in Argentina. We hypothesized that breeding focused on GY performance and broad adaptation produced an increase in crop biomass linked to an increased tolerance to adverse growing conditions, a trend associated with an increase in WUE and/or RUE. For this purpose, hybrids were grown under three stand densities and eight environmental conditions in the main target environment for the production of temperate hybrids in Argentina. Analyzed traits were GY, total shoot biomass (BT) production, harvest index (HI = GY/BT), crop evapotranspiration (ETC), crop radiation interception (IPARC: cumulative amount of intercepted incident photosynthetically active radiation), radiation use efficiency (RUE = BT/IPARC), water use efficiency (WUE) for biomass production (WUEB,ETc= BT/ETC) and WUE for GY production (WUEGY,ETc= GY/ETC). No breeding effect was registered on ETC and IPARC, whereas significant breeding effects (P < 0.05) were detected on GY (0.5 % YOR−1 from 1980 onwards). The latter were due to the improvement of BT (from 1993 onwards) as well as of HI (between 1980 and 1993), with gains of 0.5 % YOR−1 in both cases. Mentioned trends were associated with a significant increase in RUE (0.7 % YOR−1 from 1993 onwards) and consequently in WUEB,ETc (0.6 % YOR−1 from 1993 onwards) and WUEGY,ETc (0.5 % YOR−1 from 1980 onwards). Results demonstrated that breeding efforts, which have been driven almost exclusively by GY improvement, had no evident effect on the crop water use but had clear effects on crop biomass production and its partitioning. These unintended positive effects of breeding on RUE and WUEs are welcome on a global scale, considering that predicted trends of increasing human demand for water will require increased water productivity rather than increased water use by crops.